Resíduo do açaí: dos planos municipais às rotas tecnológicas - ALENCAR, Deivison de Souza (2024)
Açaí is a fruit that is part of the culture and food base of the people of Pará and is known for its nutritional and economic value to the region. The pulping of this fruit generates two main types of waste: the fibers and the stones (semestes), which are commonly disposed of inappropriately in the environment, causing various negative impacts on environmental quality and health. This scenario becomes even more challenging due to the large amount of waste generated in commercial fruit pulping establishments, considering that more than 80% of the fruit is made up of the stone. In view of the above, the aim of this research is to evaluate the technological routes for açaí stone waste in the municipal waste and sanitation plans of the state of Pará, as well as to map the descriptive technological routes for this waste in the city of Tucuruí. To this end, all the sectoral plans of Pará's municipalities were initially surveyed and analyzed by consulting specialized websites. Next, a survey instrument was applied to 44 commercial fruit pulping establishments in order to map the descriptive technological routes of the stone. The results showed that only 7.35% of the municipalities analyzed include açaí waste in their municipal sector plans, highlighting gaps in regulation and in the application of sustainable technologies. In addition, it was found that the majority of açaí beaters in Tucuruí dispose of the core inappropriately, with insufficient collection and a lack of reuse and mass and energy recovery. The conclusion is that, despite some progress in the management of açaí waste, many municipalities still lack specific regulations and effective practices. Improvements in management are proposed, encouraging the use of technologies such as composting and biofuel production, with a view to greater sustainability and reducing negative environmental impacts.